Efektivitas Model Discovery Learning terhadap Keterampilan Menulis Surat Dinas Siswa Kelas VII SMP Negeri B Srikaton - M. Syahrun Effendi; Eko Saputra (LP4MK STKIP PGRI Lubuklinggau, 2021)
This study aims to determine whether the discovery learning model is significantly effective on the writing skills of seventh grade students of SMP Negeri B Srikaton. The method used in this study was a quasi-experimental with a one group pretest-posttest design. The study population was all 7th grade students of SMP Negeri B Srikaton for the 2020/2021 academic year, totaling 236 students. One class is defined as the sample determined by the simple technique random sampling, namely class VII.6, totaling 30 students as the experimental class. Collecting data using a test technique in the form of an official letter writing test. The data analysis technique was carried out using the